1982
DOI: 10.1002/hlca.19820650114
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Synthesis, and Properties of Some Persubstituted 1,2‐Dintroethanes. In Quest of Nitrocyclopropyl‐Anion Derivatives

Abstract: Attempts to deprotonate nitrocyclopropane led to solutions which showed strong ESR. signals (Fig. 1)and from which 1‐nitro‐ l′‐nitroso‐bicyclopropyl (3) and 1,1′‐dinitro‐bicyclopropyl (2) were isolated. The activation energy for rotation about the central C, C‐bond of 2 is estimated to be about 12 kcal/mol (1 H‐NMR. spectra in Fig. 2). In contrast, the oven‐chain analogue 2,3‐dimethyl‐2,3‐dinitrobutane (1) shows a methyl singlet down to −70° C. Low‐temperature X‐ray analyses of 1, 2, 3, and also of 1,1′‐dinitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 53 publications
(21 reference statements)
1
26
0
Order By: Relevance
“…A series of tri-organophosphoniumbis(diphenylphosphino)methylides [54] and the di-tertiary phosphines derived from butadiene [55] and bicyclopropyl [56] adopt -as free ligands -ground state conformations which do not allow metal-metal contacts in their dinuclear complexes with AuCI. The former have a syn/anti conformation relative to the ylidic function (Figure 8a), and the latter two adopt the single-trans conformation (butadiene) or a form close to this extreme (bicyclopropyl) [57]. In 1:1 complexes, these conformations are retained, which is proof that phosphine coordination in principle is not necessarily associated with conformational changes.…”
Section: Ligand-supported Au Au Contacts In Non-cyclic Polynuclear mentioning
confidence: 53%
“…A series of tri-organophosphoniumbis(diphenylphosphino)methylides [54] and the di-tertiary phosphines derived from butadiene [55] and bicyclopropyl [56] adopt -as free ligands -ground state conformations which do not allow metal-metal contacts in their dinuclear complexes with AuCI. The former have a syn/anti conformation relative to the ylidic function (Figure 8a), and the latter two adopt the single-trans conformation (butadiene) or a form close to this extreme (bicyclopropyl) [57]. In 1:1 complexes, these conformations are retained, which is proof that phosphine coordination in principle is not necessarily associated with conformational changes.…”
Section: Ligand-supported Au Au Contacts In Non-cyclic Polynuclear mentioning
confidence: 53%
“…[271] R' = H, CH3 51 % Scheme 28. In situ generation and trapping of unstable enolates [48,89] and nitronates [273,274] with aromatic aldehydes with the assistance of the aldehyde adducts A [272] and B (lithiated hemi-aminal and lithiated hemi-acetal [89], respectively); the Li derivative A is usually used for the orthometalation of aromatic aldehydes [272]. In light of the instability of the enolates formed tiom the bicyclic compound shown, we conclude that this does not result from reaction of the free LiNR,, which exists in equilibrium with A, but that deprotonation, generation of the aldehyde, and aldol or nitroaldol addition result in a "collision complex" (see for example C and the accompanying caveat in the text).…”
Section: 2 LIX Adducts With Aromatic Aldehydes-in Situ Sources Of mentioning
confidence: 99%
“…Due to the low nucleo philicity of the nitronate anions, only γ iodonitropropane slowly cyclizes to nitrocyclopropane when treated with a base. 12 Recently, it was reported that the γ mesyloxy nitropropane anion reacts with imines to give substituted nitropyrrolidines 13 (Scheme 10).…”
Section: Methodsmentioning
confidence: 99%